Chemical and Organoleptic Characteristics of Skipjack Tuna (Katsuwonus Pelamis) Floss with Different Cooking Times - Deni, Sitkun; Laboroto, Supriyadi; Talib, Ahmad (Agrikan Jurnal Agribisnis Perikanan, 2024)
The purpose of this study was to determine the effect of cooking time on the chemical and organoleptic characteristics of skipjack tuna shredded fish using the cooking method (frying). The stages used in this study went through 2 (two) stages, namely, the stage of preparing raw materials and processing shredded fish and the stage of testing shredded fish. The fish floss processing stage is used with a cooking time of 2 hours, 4 hours, and 6 hours and 9 hours, the fish floss product is tested using organoleptic tests to obtain selected products, then tested using the Kruskal Wallis method and then the selected fish floss product is continued to the chemical test (proximate analysis) The results of the study showed that the results of the organoleptic test with the best value of 9 hours were appearance 8.18, aroma 8.17, taste 8.29 and texture 8.29. Then based on the results of the proximate analysis, the fish floss product with a cooking time of 9 hours showed a water content of 11.08%, ash content 5.69%, protein content 33.29% and fat 13.06%.